BANK CREDIT IN FINANCIAL PROVISION OF AGRICULTURAL ENTERPRISES - О. D. Rozhko; T. H. Marenych; V. M. Onegina; L. A. Belyayeva; O. G. Maliy (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
The implementation of strategic tasks of the agrarian sector of Ukraine essentially depends on the financial provision of agricultural producers. In the context of limitation of their own financial resources, budget financing, low development of the financial instruments recognized in the world practice, the loans of commercial banks are an important source of financial resources for agricultural enterprises and small farmers. The use of bank loans positively affects the financial and economic activities of the producers in the agrarian sector due to the opportunity of diversification of sources of financing, growth of investment activity, acceleration of capital turnover, increase of profitability of own capital, etc. Though, there are a number of factors that restrain the bank crediting to the agrarian sector in the modern terms.